Unusual cause of profound weight loss in a young woman. (22nd November 2016) - Rastogi, Ashu; Uppula, Pavan; Mukherjee, Kanchan Kumar; Bhansali, Anil
Abstract : A 27-year-old woman presented with anorexia, weight loss and psychiatric symptoms for the past 4 years. She did not have history of headache, visual disturbances or symptoms of raised intracranial pressure. She was sarcopenic with body mass index of 10.16 kg/m 2 .Her systemic examination was normal except for temporal hemianopia suggesting a sellar/suprasellar lesion. Hormonal evaluation revealed pan-hypopituitarism with central diabetes insipidus. Subsequent neuroimaging revealed sellar-suprasellar mass lesion with intense contrast enhancement and leptomeningeal metastases. Cerebrospinal fluid analysis showed elevated β human chorionic gonadotropin and the presence of syncytiotrophoblast germ cells. Histopathology from the mass lesion confirmed the diagnosis of germinoma. Immunohistochemistry of the tumour tissue was positive for c-kit and placental alkaline phosphatise. She received a combination of chemotherapy with craniospinal irradiation. Significant weight loss in a young woman may not always be an eating disorder like anorexia nervosa albeit more common than germ cell tumour.